Elementary information security - Smith, Richard E. , 1952- (Jones & Bartlett Learning, 2013)
Comprehensive and accessible, "Elementary Information Security" covers the entire range of topics required for U.S. government courseware certification NSTISSI 4013 and urges students to analyze a variety of security problems while gaining experience with basic tools of the trade